Papel da recaptação e de metabólitos da dopamina na discinesia orofacial induzida por neurolépticos em ratos - Fachinetto, Roselei (2008)
Fluphenazine-induced orofacial dyskinesia (OD) is a putative animal model of tardive dyskinesia (TD) whose pathophysiology has been related to an increase in dopamine hypersensitivity and oxidative stress. Data from literature have shown that patients with TD present a decrease in dopamine transporter (DAT) expression. In a previously study, we have demonstrated that experimental animals presenting high intensity of vacuous chewing movements (VCM) induced by chronic treatment with haloperidol also presented a reduced dopamine uptake into striatum. Considering that one way to regulate DAT is through redox modulation, the first objective of the present study to determine if the chronic treatment with fluphenazine could induce an increase in oxidative stress index in brain regions (striatum and substantia nigra) and an alteration in levels of dopamine uptake in the striatum of rats treated acute and chronically with fluphenazine (Article 1). The fluphenazine treatment produced VCMs in the majority of the treated rats (87% after 24 weeks). Concomitant treatment with diphenyl diselenide decreased the prevalence of VCMs to 50%. Additionally, we separated the rats that developed (+VCM) or did not develop (-VCM) VCMs. We did not find any statistical differences among the groups when oxidative stress parameters were evaluated. Chronic fluphenazine treatment significantly decreased dopamine uptake. Concomitant treatment with diphenyl diselenide was not able to prevent this decrease in those rats that developed VCMs. Another objective of this work was to evaluate the role of dopamine (DA) and other monoamines and their metabolites on acute and chronic of OD induced by fluphenazine in rats (manuscript in preparation 1). The vacuous chewing movements (VCMs) or the levels of monoamines and its metabolites were quantified after 3 (acute) or 24 (chronic) weeks after beginning of treatment. The fluphenazine treatment produced VCMs in part of treated rats (50% after 3 weeks and about 85% after 24 weeks). There were not significant differences between the groups in monoamines levels neither in their metabolites in the striatum under acute fluphenazine treatment in +VCMs rats. However, we observed a trend to increase the levels of the DA metabolites, HVA (p=0.05) and DOPAC (p=0.06), after chronic treatment with fluphenazine. Our data suggest that an increase in DA metabolism could contribute to the maintenance of VCMs in rats. Moreover, development of VCMs seems not to be dependent of DA metabolism. Moreover, the use of diphenyl disselenide seems to be a promissory pharmacological therapy in the reduction of OD prevalence.